Social return on investment in the public sector. Issue 3 (15th April 2020) - Vluggen, Rob; Kuijpers, Relus; Semeijn, Janjaap; Gelderman, Cees J.
Abstract : Purpose: Social return on investment (SROI) is a systematic way of incorporating social values of different stakeholders into public sector decision-making on sustainability. This study aims to identify salient factors that influence SROI implementation. Design/methodology/approach: The interactions of four Dutch municipalities and their social enterprises were examined, by analyzing relevant documents and interviewing key actors. Findings: External forces appear to have little influence on SROI implementation. Management systems, legal restrictions in relation to privacy and the administrative burden appear to hinder SROI implementation. Findings suggest that trust among the parties involved and their representatives is a major driver for SROI development. SROI is not measured well enough, which complicates analyzing and reporting its development. Research limitations/implications: Achieving collaboration through trust is a characteristic of stewardship theory, and therefore useful for studying social sustainability. Combining agency and stewardship theory provides useful insights concerning the application of control mechanisms versus empowerment. Practical implications: Barriers can be overcome by informing and engaging suppliers in SROI initiatives. Furthermore, findings of this study suggest that it is easier for municipalities to incorporate SROI when social firm activities are insourced. An independent procurement function stimulates SROI development. Engaged professionals can make the difference in SROI policy implementation, more so than written policies. Social implications: SROI enables social sustainability. SROI can be used by public agencies to provide meaningful activities for the long-term unemployed and underprivileged adolescents. Originality/value: The study is the first empirical work that relates public procurement to SROI implementation and its effect on suppliers. The findings provide valuable insights into government influence on social enterprises.